TASPO Member to Marry P-of-S Nurse Shortly - Unknown (Evening News)
Mr. Elliot "Ellie" Manette, machinist and leader of the Invaders Steel Band, will marry Miss Joyce Cumberbatch, a nurse. Mr. Manette, a TASPO member, returned to Trinidad from a tour of England and France. Other wedding notices appeared in the article.
Keywords: Musicians -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Steel bands (Music) -- Trinidad and Tobago